Surface water purification for drinking purposes using mechanical mixing and settling tanks with Plate Settlers - Debs, Tasnim; Hossam Sabouh (Latakia University Journal -Engineering Sciences Series, 2022)
Coagulation, flocculation, and sedimentation are the most common processes for drinking water purification from surface sources. Therefore, there is a great tendency to improve these processes and study the parameters affecting them. Thus, this study aims to find the optimal values of the main design parameters of both the coagulation and flocculation processes using the mechanical mixing method. The research included conducting a wide range of experiments on raw water samples taken from Lake Tishreen Dam 16 with medium and high turbidity, whose values were as follows: (100-200-300-400-500-600mg/l), and the coagulant used was alum (aluminum sulfate ). The optimal dose for each turbidity was determined using the principle of experimental coagulation (Jar-Test). The optimal values for the mixing time and the velocity gradient of the rapid mixing process (mixing) ranged according to the results of the experiments within the following values : (T1 = 25-55 sec) and (G1 = 180-300 sec-1), while the optimal values for the mixing time and the velocity gradient of the slow mixing process (flocculation process) are as follows: (T2 = 540–1080 sec) and (G2 = 25–55 sec-1) according to the turbidity of the raw water used in the experimental work. Based on the results of these tests, a laboratory model was designed for a compact purification unit that adopts the principle of sedimentation using inclined plates and was tested to evaluate the effectiveness of its work when following the method of mechanical mixing and sedimentation in two cases using inclined plates and without them. The results of the proposed purification unit test demonstrated the effectiveness of the applied mechanism for purifying surface water, as the residual turbidity at the optimum values of the parameters taken into account did not exceed the limits that allow water to flow into the filters in order to remove its residual turbidity, which ranges between (8-15 mg/l). The presence of inclined plates within the sedimentation basins led to a greater removal of turbidity compared with those without plates.